The Implementation of Read, Encode, Annotate, adn Ponder (REAP) Strategy To Improve Students’ Reading Comprehension: (A Classroom Action Research to the Tenth Grade Students of SMA Negeri 1 Kayan Hulu in Academic Year 2021/2022) - Putra, Andreas Dandy; Yuliana, Yohanes Gatot Sutapa; Wardah, Wardah; Sada, Clarry; Rezeki, Yanti Sri (Kirana Publisher (KNPub), 2023)
This research aims to improve students’ reading comprehension of narrative text by using Read, Encode, Annotate, and Ponder (REAP) strategy. This research is a classroom action research which was conducted in three cycles. The participants of this research are the teacher and the students in class X IIS 4 of SMA Negeri 1 Kayan Hulu.The study showed that the use of REAP strategy gave significant improvement in students’ reading comprehension of narrative text. Before implementing the strategy, the students’ understanding of the text were not well structured because they could not comprehend the text or story clearly. They were not motivated to read and comprehend the text. The students’ problems solved when the researcher implemented REAP strategy for teaching and learning. REAP strategy gave an active process of reading which can help students to construct their greater understanding about the text. It was shown by students’ enthusiasm to pay attention in doing every activity during teaching and learning process used REAP strategy. Furthermore, the students showed motivation and enthusiasm during the learning phase of teaching. In conclusion, the use of REAP strategy could enhance students’ reading comprehension of narrative text.